1963
DOI: 10.2466/pr0.1963.12.3.695
|View full text |Cite
|
Sign up to set email alerts
|

Constant vs Varied Serial Order in Paired-Associate Learning

Abstract: Typical varied serial-order conditions of paired-associate (PA) learning were compared with a constant serial order on all trials in 5 experiments involving systematic variations in method, kind of material, and other potentially relevant factors. The results showed a small but relatively consistent facilitation by constant serial order limited primarily to later stages of learning. Since a shift following the first correct response to each pair from constant to varied serial order produced as much facilitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

1966
1966
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…In summary, taking all of the present findings together, one may conclude that the retention interval hypothesis expects either that (a) the study-test method be superior to the anticipation method, or that (b) both learning procedures may produce about the same levels of performance under a constant item presentation order, in a manner similar to the random one, from the same theoretical rationale based on critical items that enter STM at the end of the study event. The present nonsignificant differences between the two learning methods and those of Battig et al (1963, Experiment 1) support (b) above, and the overall superiority for the study-test method over the anticipation method by Battig et al (1963, Experiment 4) and Izawa (1979a) is in agreement with (a) above. Thus, the data seem to support both types of expectations from the retention interval hypothesis under a constant item presentation order.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In summary, taking all of the present findings together, one may conclude that the retention interval hypothesis expects either that (a) the study-test method be superior to the anticipation method, or that (b) both learning procedures may produce about the same levels of performance under a constant item presentation order, in a manner similar to the random one, from the same theoretical rationale based on critical items that enter STM at the end of the study event. The present nonsignificant differences between the two learning methods and those of Battig et al (1963, Experiment 1) support (b) above, and the overall superiority for the study-test method over the anticipation method by Battig et al (1963, Experiment 4) and Izawa (1979a) is in agreement with (a) above. Thus, the data seem to support both types of expectations from the retention interval hypothesis under a constant item presentation order.…”
Section: Resultssupporting
confidence: 86%
“…This implies the possibility of similar performance levels for both constant and random item presentation orders within each method. There are indeed, data supporting this expectation, as seen in e. g., Battig, Brown and Nelson (1963). On the other hand, there are grounds to expect superior performance for a constant order vis-a-vis a random one within each method: (a) The constant groups enjoy facilitation stemming from serial order cues, which is absent in the random groups; (b) whereas the random order conditions suffer from considerable variations in the length of the retention interval, such variations are absent in the constant conditions.…”
Section: With a Constant Item Presentation Ordersupporting
confidence: 58%
“…The authors argue that the data did not indicate serial learning, but rather that position represented a discriminative cue with which already learned pairs could be associated. In a subsequent experiment (Battig, Brown, & Nelson, 1963), it would found that the amount of facilitation obtained with position constancy contingent upon the appearance of a correct response was equivalent to that obtained with items in constant position from the outset. Serial position, like frequency, has effects only after associations have been acquired.…”
Section: Interference Among Memory Traces 151mentioning
confidence: 99%
“…Martin and Saltz (1963) showed significant transfer from the S(S) and S(R) conditions to a derived serial list of the response terms which maintained the constant order of the paired-associate study trials. Although these authors concluded that serial associations had therefore been learned during pairedassociate training, Battig, Brown, and Nelson (1963) failed to replicate such positive transfer among roughly comparable conditions. It is, however, with the effects of constant serial presentation upon paired-associate learning itself that the present study is concerned.…”
mentioning
confidence: 94%